Survey Finds Gender Disparities Impact Both Women Mentors and Mentees in Gastroenterology. (18th September 2021) - Rabinowitz, Loren Galler; Grinspan, Lauren Tal; Zylberberg, Haley M.; Dixon, Rebekah; David, Yakira N.; Aroniadis, Olga C.; Chiang, Austin; Christie, Jennifer; Fayad, Nabil F.; Ha, Christina; Harris, Lucinda A.; Ko, Cynthia W.; et al.
Abstract : INTRODUCTION: Gastroenterologists at all levels of practice benefit from formal mentoring. Much of the current literature on mentoring in gastroenterology is based on expert opinion rather than data. In this study, we aimed to identify gender-related barriers to successful mentoring relationships from the mentor and mentee perspectives. METHODS: A voluntary, web-based survey was distributed to physicians at 20 academic institutions across the United States. Overall, 796 gastroenterology fellows and faculty received the survey link, with 334 physicians responding to the survey (42% response rate), of whom 299 (90%; 129 women and 170 men) completed mentorship questions and were included in analysis. RESULTS: Responses of women and men were compared. Compared with men, more women preferred a mentor of the same gender (38.6% women vs 4.2% men, P < 0.0001) but less often had one (45.5% vs 70.2%, P < 0.0001). Women also reported having more difficulty finding a mentor (44.4% vs 16.0%, P < 0.0001) and more often cited inability to identify a mentor of the same gender as a contributing factor (12.8% vs 0.9%, P = 0.0004). More women mentors felt comfortable advising women mentees about work-life balance (88.3% vs 63.8%, P = 0.0005). Nonetheless, fewer women considered themselves effective mentors (33.3% vs 52.6%, P = 0.03). More women reported feeling pressured to mentor because of their gender (39.5% vs 0.9% of men, P < 0.0001). Despite no gender differences, one-third of respondents reported negative impact of the COVID-19 pandemic on their ability to mentor and be mentored. DISCUSSION: Inequities exist in the experiences of women mentees and mentors in gastroenterology, which may affect career advancement and job satisfaction. Abstract :